Mediación TIC usando tabletas para fortalecer la calidad educativa en las instituciones de Providencia Isla (2019)
The purpose of this research project is to design a pedagogical proposal mediated by Information and Communication Technology (ICT) with the use of tablets for the strengthening of educational quality in Providencia Educational Institutions, taking as a reference the synthetic index quality. Based on the pedagogical practices of the María Inmaculada Educational Institution where emphasis is placed on research and reading comprehension in all areas, however, the educational use of technologies is incipient, a situation that is worrisome due to the impact of technological tools they have in the quality of the academic and administrative processes. The research is conducted under a mixed approach, descriptive type, quasi-experimental method, a sample of 8 teachers from the Spanish area and primary and secondary basic mathematics from a population of 12 teachers was selected. group of 28 students of the seventh grade from a population of 265 students, to whom a survey was applied to verify the degree of educational appropriation of the ICTs of the María Inmaculada Educational Institution; Likewise, a documentary review was carried out to collect Institutional information related to the synthetic quality indicators established by the Ministry of National Education of Colombia regarding the 4 components: Progress, Performance, Efficiency and School Environment. The main results obtained show that the Institution has been improving its performance and the quality of its processes between 2016 and 2017, as it is observed in the performance agreement for excellence sent by the Ministry of Education and endorsed by Decree 1075 of the 2015, whenever there is a minimum annual improvement at all levels of an Institution, which is signed by the Rector of the Institution. It was concluded that Providence Island is seeing the results of actions and strategies applied to improve quality, with the use of tablets in classrooms by teachers, which has an impact on the improvement of students' competitiveness and in the empowerment of teachers of their daily work for the benefit of themselves and the community in general through the pedagogical use of technological tools and the appropriation of innovative methodologies. Theories that were used in the project, the main results obtained by each objective and the main conclusions. The constructivist theory is the one that was worked on, the theory of significant learning and the theory of the digital